Pengembangan âPractice Set Siklus Akuntansi Perusahaan Dagangâ (SIAKUPEDE) untuk Mahasiswa Program Studi Akuntansi - Nugroho, Tatas Ridho; Dwihandoko, Toto Heru (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2018)
The purpose of this study was to produce prototypes of teaching materials in the form of "Practice Set Cycle of Trade Company Accounting" (SIAKUPEDE) Computer-based valid, practical and effective for economics faculty accounting students at Majapahit Islamic University. The development model used in developing this learning tool is the Thiagarajan Semmel and Semmel model, better known as the 4-D (Four-D) model, which consists of: (1) Define (defining) stage, (2) Design Phase (Design ), (3) Stage of Development (Development) and (4) Disseminate stage (spread). The results of the validation of material experts on SIAKUPEDE are indicated by a percentage of 78.12% (valid). Likewise, the results of the validation of the SIAKUPEDE 95.83% (very valid) material. Furthermore, the results of individual tests (readability) of the SIAKUPEDE are found in the form of errors in writing. Furthermore, the field test shows 100% included in very practical criteria to be implemented. The results of the pre-test and post-test assessment showed significant changes where the average pre-test score was 46 and the post-test score was 84 or experienced an increase. The average post-test score is above the defined KKM, meaning that the use of the SIAKUPEDE is said to be effective in improving student learning outcomes